Genetic diversity in Amazonian Jundiá (Leiarius marmoratus) stocks using heterologous primers - Laís Santana Celestino Mantovani; Felipe Pinheiro de Souza; Eric Costa Campos; Vanessa Lewandowski; Nelson Maurício Lopera Barrero; Ricardo Pereira Ribeiro (Acta Scientiarum. Animal Sciences, 2021)
With the rise of world fish farming, the national scenario is favorable for using native fish for intensive farming. Among the catfish, the Amazonian Jundiá (Leiarius marmoratus) is a robust candidate, easy to grow and with good organoleptic characteristics in its flesh. For productive success in captivity, it is necessary to consider some questions about the species, such as genetic variability, which must have an acceptable level in a breeding stock, in order to maintain a good diversity; this reduces losses due to inbreeding and low diversity. Therefore, the objective of this study was to characterize the genetic variability of commercial stocks of L. marmoratus from the State of Mato Grosso through microsatellite molecular markers. We analyzed 143 individuals from three stocks. The mean heterozygosity and the inbreeding coefficients observed were 0.060; 0.084; 0.141; and 0.539; 0.562; 0.514, respectively, for the stocks of Campo Verde, Juína, and Nova Mutum. The Deviation in the Hardy-Weinberg equilibrium was observed in most of the loci in the three populations. Considering the genetic differentiation, it is concluded that the three populations are very close genetically, which requires introduction of new genetic material in the stocks to enrich them genetically for a later reproductive program.